2016
DOI: 10.1080/21541248.2016.1181698
|View full text |Cite
|
Sign up to set email alerts
|

Isoform-specific targeting of ROCK proteins in immune cells

Abstract: Rho-associated kinase 1 (ROCK1) and ROCK2 are activated by Rho GTPase and control cytoskeleton rearrangement through modulating the phosphorylation of their down-stream effector molecules. Although these 2 isoforms share more than 90% homology within their kinase domain the question of whether ROCK proteins function identically in different cell types is not clear. By using both pharmacological inhibition and genetic knockdown approaches recent studies suggest that the ROCK2 isoform plays an exclusive role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 38 publications
(52 reference statements)
0
33
0
Order By: Relevance
“…ROCK is a key regulator of actin organization and thus a regulator of cell migration [46]. The function of ROCK in macrophage regulation 20 is contradictory [19,47]. Our studies demonstrated that ROCK inhibitor could polarize macrophage to M2 phenotype and protect the liver from IRI.…”
Section: Discussionmentioning
confidence: 86%
“…ROCK is a key regulator of actin organization and thus a regulator of cell migration [46]. The function of ROCK in macrophage regulation 20 is contradictory [19,47]. Our studies demonstrated that ROCK inhibitor could polarize macrophage to M2 phenotype and protect the liver from IRI.…”
Section: Discussionmentioning
confidence: 86%
“…KD025, published in 2008, is the first highly selective ROCK2-isoform inhibitor. 17,[63][64][65][66] In addition to the pro-beige adipogenic action of KD025, we have noticed an anti-adipogenic action of KD025 as reflected by reduced perilipin levels in the drug-treated SV cells ( Figure 7D, 7). Indeed, its therapeutic potential has been explored in fibrotic disease, 15 focal cerebral ischemia, 16,61,62 and auto-immune disease.…”
Section: Discussionmentioning
confidence: 88%
“…Indeed, its therapeutic potential has been explored in fibrotic disease, 15 focal cerebral ischemia, 16,61,62 and auto-immune disease. 17,[63][64][65][66] In addition to the pro-beige adipogenic action of KD025, we have noticed an anti-adipogenic action of KD025 as reflected by reduced perilipin levels in the drug-treated SV cells ( Figure 7D, 7). Importantly, both dose-and time-dependent analyses ( Figure 7E; Figure S8A) helped to dissociate the pro-beige adipogenic (mediated by ROCK2 inhibition) and anti-adipogenic (targets are not clear) actions of KD025.…”
Section: Discussionmentioning
confidence: 88%
“…therapies reassures that macular edema is maximally treated. Future therapies should be focused on deactivating inflammatory cells [24,25].…”
Section: Expert Opinionmentioning
confidence: 99%